Japanese financial growth - Goodhart, Charles A. E. (Macmillan, 1990)
This book is a collection of papers presented at the international conference on Japanese financial growth. This was the fifth confeence organised by permanent advisory committee on Eurodollar in co-operation with the London school of economics financial markets group.